297 Leap-005: evaluating the safety and efficacy of lenvatinib and pembrolizumab in patients previously treated for ovarian cancer, a multi-cohort phase 2 study. (4th December 2020) - Gonzalez-Martin, Antonio; Chung, Hyun Cheol; Saada-Bouzid, Esma; Yanez, Eduardo; Senellart, Hélène; Cassier, Philippe A; Basu, Bristi; Ghori, Razi; Kubiak, Peter; Smith, Alan; Norwood, Kevin; Lwin, Zarnie
Abstract : Introduction/Background: Lenvatinib, an antiangiogenic multiple receptor tyrosine kinase inhibitor, plus pembrolizumab, a programmed death-1 immune checkpoint inhibitor, demonstrated promising clinical benefit in a previous phase Ib/II trial across several cancer types (ClinicalTrials.gov, NCT02501096 ). We assessed clinical outcomes with lenvatinib plus pembrolizumab in patients with ovarian cancer in the ongoing, open-label, multicohort, phase II LEAP-005 study (ClinicalTrials.gov, NCT03797326 ). Methodology: Female patients aged ≥18 years with histologically/cytologically confirmed metastatic/unresectable ovarian cancer, measurable disease per Response Evaluation Criteria in Solid Tumors (RECIST v1.1), Eastern Cooperative Oncology Group (ECOG) performance status 0/1, and 3 prior lines of therapy were enrolled. Patients received lenvatinib 20 mg daily plus pembrolizumab 200 mg every 3 weeks for 35 cycles, or until confirmed disease progression or unacceptable toxicity. Primary endpoints were objective response rate (ORR; response assessed every 9 weeks for 54 weeks, then every 12 weeks, by blinded independent central review per RECIST v1.1) and safety. Secondary endpoints included disease control rate, duration of response, and progression-free survival. Results: 31 patients with ovarian cancer received ≥1 dose of lenvatinib plus pembrolizumab in LEAP-005 (median age 62 years [range 40–76]); median study follow-up was 7.8 months (range, 4.6–12.4) as of April 10, 2020. ORR was 32% (95% confidence interval, 17–51); other efficacy endpoints were also favorable (table 1 ). Treatment-related adverse events occurred in 29 (94%) patients (table 1 ). Conclusion: Lenvatinib plus pembrolizumab demonstrated encouraging efficacy and manageable safety in patients with heavily pretreated ovarian cancer, including those with prior platinum failure and those with previous bevacizumab exposure. Disclosures: Antonio González-Martín: Advisory/Consultancy: Amgen, AstraZeneca, Clovis Oncology, Genmab, GSK, ImmunoGen, Mersana, Merck Sharp & Dohme, Novartis, Oncoinvent, Pfizer/Merck, PharmaMar, Roche, Sotio; Speaker Bureau: AstraZeneca, PharmaMar, Roche, GSK; Research Grant/Funding: Roche, TESARO: A GSK Company; Travel/Accommodation/Expenses: AstraZeneca, PharmaMar, Roche, TESARO: A GSK Company Hyun Cheol Chung: Grants/Research Support: Lilly, GSK, MSD, Merck-Serono, BMS/Ono, Taiho, Amgen, Beigene, Incyte; Honoraria: Merck-Serono, Lilly/Foundation Medicine; Consultation: Taiho, Celltrion, MSD, Lilly, Quintiles, BMS, Merck-Serono, Gloria, Beigene, Amgen, Zymework Esma Saada-Bouzid: Advisory/Consultancy: BMS, MSD; Travel/Accommodation: AstraZeneca, BMS, MSD Eduardo Yanez: Consultant/Advisory Board: BMS, Merck Serono; Research Grant: Amgen, Pfizer, Astellas, BMS, Roche, Abbvie, MSD Hélène Senellart: Nothing to disclose. Philippe A. Cassier: Honoraria: Novartis, Roche/Genentech, Blueprint Medicines, Amgen, AstraZeneca; Research Funding: Novartis, Roche/Genentech, Lilly, Blueprint Medicines, Bayer, AstraZeneca, Celgene, Plexxikon, Abbvie, BMS, Merck Serono, MSD, Taiho Pharmaceutical, Toray Industries, Transgene, Loxo, GSK, Innate Pharma, Janssen (all paid to institution); Travel, Accomodations, Expenses: Roche, Amgen, Novartis, BMS, MSD, Netris Pharma. Bristi Basu: Consultancy: GenMab (paid to institution); Advisory Board: Roche, Eisai Europe Limited, research grant from Celgene Ltd (all paid to institution); Speakers Bureau: Eisai Europe Ltd (paid to institution); Travel and Registration for Congress: Bayer. Razi Ghori: employee of Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA Peter Kubiak: employee of Eisai Inc., Woodcliff Lake, NJ, USA Alan Smith: employee of Eisai Ltd., Hatfield, UK Kevin Norwood: employee of Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA Zarnie Lwin: Received honoraria for consulting, advisory role or travel sponsorship from AbbVie; AstraZeneca; BMS; Roche; and Merck